Pricing for a Cooler Planet: An Empirical Analysis of the Effect of Taxing Carbon - Torben K. Mideksa (Center for Economic Studies and ifo Institute (CESifo), 2021)
Finland introduced the planet's first carbon tax in 1990 to experiment with, to most economists, the best policy to reverse carbon emissions. I estimate the causal effect of taxing carbon on Finnish emissions using the Synthetic Control Approach (Abadie, 2021). The results suggest that taxing carbon reduces emissions by big margins. Finnish emissions are 16% lower in 1995, 25% lower in 2000, and 30% lower in 2004 than emissions in the counterfactual consistent with carbon taxes whose value increasing by 20 fold in 1990 - 2005. The estimates suggest that the carbon tax's abatement elasticity is about 9%.
Keywords: C21; C23; H23; L91; Q54; Q58; 330